THEORETICAL FOUNDATIONS OF THE CONCEPT OF "FINANCIAL STABILITY" - Sattarov Tulkin Abdikhalilovich (Scholar Express Journals, 2025)
This article examines the methodological foundations for justifying the term “stability” and highlights its distinctive features compared to other related terms such as “sustainability”, “security”, and others. By relying on the views of economists with substantial expertise in this field, the author establishes his own perspective on the problem under study.
Keywords: Stability; sustainability; development